THE LIVED EXPERIENCES OF COLLEGE TEACHERS ON THE USE OF SOCIAL MEDIA IN TEACHING. - Janet Alesna Mananay (International Journal of Research Science and Management, 2018)
Lectures and other traditional teaching methodologies employed by University faculty have come to be scrutinized for their impersonal approach especially in this modern digital age. Recently, social media or academic networking sites have become increasingly popular as learning and teaching resources in higher education, providing students with increased opportunities for educational engagement. This research endeavors to discuss the extent of use of social media among college instructors and professorsin their instructionallearning praxis. The participants were 10 faculty of the College of Teacher Education. To gather data, they underwent FGD and semi structured interview. The results showed (1) Teachers use social media in education because of its convenience and significance. (2) Social media as a teaching tool is effective because students are engaged and connected. (3) There are challenges hurdled in the use of social media such as Internet connection and privacy issues. The study recommends that higher education adopt the flipped classroom format, as using social media is found to be effective. Furthermore, higher education institutions may cox the educational technology decisions and policy to accommodate digital tools in teaching and learning in the 21st century